Lost dignity: predominant experience of old age by the elderly - Leila Sadeghmoghadam; Mahshid Foroughan; Farahnaz Mohammadi Shahboulaghi; Fazlollah Ahmadi; Akram Farhadi; Shima Nazari; Masoumeh Amiri Delui (Journal of Research & Health, 2019)
Paying attention to the views of the elderly and identifying their understanding of old age can be great help for proper consideration about their needs and problems. The purpose of this study was to understand the predominant experience of elderly people of aging. Hermeneutics phenomenology was used to collect data, and the van Manen's method was implemented to analyze those data. The required data was collected by having 10 deep semi-structured interviews with the elderly from Tehran, Mashhad and Gonabad– cities, Iran, and then was analyzed for the explanation of the notion of old-age.Three views that were extracted aging agony, lost independence and marginalization. These can reflect the negative viewpoints of the elderly about the aging phenomenon. The elderly’s aging description can provide experts and employees in various sanitary, training and social departments with invaluable data in order to decrease the current problems facing the elderly to plan for their future and better communicate with them, and finally enhance the available knowledge about elderly and their quality of life.